2017
DOI: 10.1016/j.apjtm.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal disease, a clinical and epidemiological review

Abstract: Meningococcal disease is the acute infection caused by Neisseria meningitidis, which has humans as the only natural host. The disease is widespread around the globe and is known for its epidemical potential and high rates of lethality and morbidity. The highest number of cases of the disease is registered in the semi-arid regions of sub-Saharan Africa. In Brazil, it is endemic with occasional outbreaks, epidemics and sporadic cases occurring throughout the year, especially in the winter. The major epidemics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 84 publications
2
56
0
6
Order By: Relevance
“…Primary meningococcal pneumonia tends to be more common in adults (>50 years old) and associated with serogroups W or Y [1]. Across all serogroups, IMD presenting as primary pneumonia occurs only 5% to 10% of the time [2]. In England and Wales (2010-2015), bacteremic pneumonia was observed in 12% of MenW IMD cases and was more common in individuals ⩾45 years old, at 20%.…”
Section: Pneumonia and Upper Respiratory Tract Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary meningococcal pneumonia tends to be more common in adults (>50 years old) and associated with serogroups W or Y [1]. Across all serogroups, IMD presenting as primary pneumonia occurs only 5% to 10% of the time [2]. In England and Wales (2010-2015), bacteremic pneumonia was observed in 12% of MenW IMD cases and was more common in individuals ⩾45 years old, at 20%.…”
Section: Pneumonia and Upper Respiratory Tract Infectionsmentioning
confidence: 99%
“…All of Chile's MenW IMD cases in 2013 were caused by ST-11 [33]. At early stages, meningococcal disease usually presents as cold-like symptoms, including sore throat, cough, coryza and otalgia [2]. This often results in IMD being indistinguishable from a viral infection in its first 4 to 6 h. Viral infection may make individuals more susceptible to invasion of N. meningitidis, leading to IMD.…”
Section: Pneumonia and Upper Respiratory Tract Infectionsmentioning
confidence: 99%
“…He denied any significant symptoms of urinary tract infection, acute intraabdominal infection, and meningitis. In a study by Rodrigo Siqueira Batista et al [5], symptoms such as sore throat, coryza, cough, and otalgia were found after the incubation period. The classic symptoms occurred only in 44% of patients and were also more common in Streptococcus pneumoniae infection [6].…”
Section: Discussionmentioning
confidence: 96%
“…Os principais fatores de virulência do meningococo são: 1) a cápsula polissacarídica (na qual baseia-se a classificação em sorogrupos); 2) proteínas de membrana externa que incluem pili tipo IV, as porinas (PorA e PorB) e moléculas de adesão, Opc; 3) mecanismos de sequestro de ferro; e 4) endotoxinas (lipopolissacárides) (Batista et al, 2017). A classificação das cepas em sorosubtipos, sorotipos e imunotipos é baseada na proteína de membrana externa classe 1 (PorA), proteína de membrana externa classe 2 ou 3 (PorB) e estrutura dos lipopolissacarídes, respectivamente (Stephens, 2009;Pollard & Frasch, 2001).…”
Section: Introductionunclassified
“…A doença meningocócica é endêmica no Brasil, com a ocorrência periódica de epidemias. Registraram-se quatro surtos epidêmicas ao longo do tempo: 1) 1920 a 1925 (sorogrupo A); 2) 1945 a 1951 (sorogrupo A); 3) 1971 a 1977 (sorogrupos C e A) e 4) 1988 a 2002 (sorogrupos B e C) (Batista et al, 2017). As epidemias causadas pelo sorogrupo A nos anos 1920 e 1940, atingiram taxas de incidência de 12 a 25 casos/100.000 habitantes.…”
Section: Introductionunclassified